Revealing the electronic band structure of quasi-free trilayer graphene on SiC(0001). Issue 1693 (19th June 2014) - Coletti, C.; Forti, S.; Principi, A.; Emtsev, K.V.; Zakharov, A.A.; Daniels, K.M.; Daas, B.K.; Chandrashekhar, M.V.S.; MacDonald, A.H.; Polini, M.; Starke, U.
ABSTRACT: Recently, much attention has been devoted to trilayer graphene because it displays stacking and electric field dependent electronic properties well-suited for electronic and photonic applications [1-8]. Several theoretical studies have predicted the electronic dispersion of Bernal (ABA) and rhombohedral (ABC) stacked trilayers. However, a direct experimental visualization of a well-resolved band structure has not yet been reported. In this work, we obtain large area highly homogenous quasi-free trilayer graphene (TLG) on 6H-SiC(0001) and measure its electronic bands via angle resolved photoemission spectroscopy (ARPES). We demonstrate by low energy electron microscopy measurements that that trilayer domains on SiC extend over areas of tens of square micrometers. By fitting tight-binding bands to the experimental data we extract the interatomic hopping parameters for Bernal and rhombohedral stacked trilayers. For ABC stacks and in the presence of an electrostatic asymmetry, we detect the existence of a band-gap of about 120 meV. Notably our results suggest that on SiC substrates the occurrence of ABC-stacked TLG is significantly higher than in natural bulk graphite. Hence, growing TLG on SiC might be the answer to the challenge of controllably synthesizing ABC-stacked trilayer – an ideal material for the fabrication of a new class of gap-tunable devices.